The influence of cognitive styles on the interaction with a language instruction CD-ROM : a case study of Malaysian ESL learners - Ng, L.L. (2012)
In postcolonial multilingual societies, matters of education are deeply rooted in the discourse of ethnicity. In Malaysia, the interface between ethnicity and education is reflected in recent debates on the choice of medium of instruction (MOI). In 2002, the Malaysian government introduced English as MOI by replacing Malay, the national language, for teaching mathematics and science, at the school level. However, in 2009, the policy was reversed to Malay. This policy initiative has been actively contested in the Malaysian media. Through an analysis of news reports on the controversy published by the Malaysian Chinese newspaper, Nanyang Siang Pao, this paper aims to illustrate how a sizeable ethnic minority is able to position itself vis-à-vis a national policy. To explain the ethno-political construction of MOI debates in the newspaper, we use two concepts, namely, ‘plurality of struggles’ (Laclau, 2006a, 2006b; Laclau & Mouffe, 1985) and ‘transmission of the speech of others’ (Bakhtin, 1981). These notions are contextualized in the macro-context of a multi-ethnic polity in which Chinese society, Chinese press and Chinese education are seen to co-construct community interests.